Quinta do Prado Verde - Habitar a Natureza - Pedro Jarmela Marques (2018)
This Master's thesis entitled "Quinta do Prado Verde-Habitar a Natureza" seeks to draw attention and highlight the importance of the relationship between Man and Nature. This architecture project intends to make this connection in order to maintain the identity of each of the parts. It begins with an approach to the behaviours that result from life in society, warnings about today's metropolis and also the signs of danger emerging from technology. This reflection is continued, addressing some of the most appealing aspects of nature. Some examples and references that are based on the natural context are analysed. Ultimately, it intends to materialize the union of the Man- Nature concept presenting a practical proposal that exploits the dialectic between the world intervened and constructed by Man and the natural world in a dialogue, of harmony and respect, preserving its characteristics and its essence.